Perancangan Sistem Informasi Pemesanan Tiket Kereta Api Layanan Lokal Bandung Raya Berbasis Aplikasi KAI Accsess (Studi Kasus pada PT KAI) - Hannan, Aulia Alfita (Ebiz Prima Nusa, 2023)
The management information system (MIS) is an implementation of information technology that is used, including the transportation sector. PT KAI as a train provider uses an information system to support its business activities, one of which is a train ticket booking application through KAI Access. The entire system of KAI Access is running well, but there are a few deficiencies regarding the output expected from users of this service to make travel more effective and efficient. The drawbacks of this output are in the form of the absence of train track information on the E-ticket and notification of train arrivals in real time in the Application.Therefore it is necessary to design an information system by making a wellstructured project design so that the results obtained by the KAI Access Application user service are maximized. The design is done by first describing business processes using BPMN and designing solutions using Data Flow Diagrams (DFD).